STUDI ETNOBOTANI PADA MAKANAN KHAS SUKU BATAK TOBA DI DESA PANGKALAN LIBUT KECAMATAN PINGGIR KABUPATEN BENGKALIS PROVINSI RIAU - Sri Wahyuni; Al Khudri Sembiring; Ade Paldo Manullang; Marta Dinata; Mar'atul Afidah (Bio-Lectura : Jurnal Pendidikan Biologi, 2022)
Plants in typical food ethnobotany such as Arsik, Lappet, Itak, and Saksang are an assimilation process by the Toba Batak tribe in utilizing plants. This study reveals what types of plants, plant parts and how the processing of typical foods and their meanings are by the Toba Batak people in Pangkalan Libut Village. The sampling of the research was carried out using a Porposive Sampling technique, which involved 4 people in Pangkalan Libut Village, especially the Toba Batak Tribe. Data were collected using interview techniques and data were processed using formulas and made in the form of diagrams. The results showed that there were 23 plant species used by the Toba Batak people in Pangkalan Libut Village in making special foods, and the plant parts used were roots, stems, fruit, flowers, seeds, leaves, rhizomes, and tubers with Zingiberaceae family as the largest family. 18% used and the least used family, namely the Apiaceae family, 4%, and the plant parts used were roots, stems, fruit, flowers, seeds, leaves, rhizomes, and tubers with the meaning of expressing gratitude for each special food, namely as a thanksgiving made during the Literacy - literacy event, Wages - wages, horse - horse panaekkhon, Malua and Ulaon pasu - pasu. From the results of the study it can be found that the typical food of the Toba Batak Tribe has gone through a process of assimilation so that changes in ingredients and meanings occur, but the Toba Batak people still preserve Arsik, Lappet, Itak, and Saksang by using plants as typical food ingredients and are able to survive. to date.